Echoes of Silence: Unmasking Workplace Discrimination Against Female Paramedic Professionals in Health Care Institutions: Echoes of Silence in Workplace Discrimination - Janjua, Mahham; Khurram, Nosheen; Yaseen, Sadia; Maryam, Attka (ADVANCES IN BASIC MEDICAL SCIENCES, 2024)
Objectives: Workplace discrimination is a pervasive phenomenon. Female paramedics, play a crucial role in our healthcare system, often face such discrimination but there is a notable lack of comprehensive data. This study assesses workplace discrimination among female paramedic professionals using the everyday discrimination scale, explores its relationship with demographics age, job title, duty hours, pay scale and identifies differences in discrimination experiences across key variables in public and private healthcare institutions. Methodology: This cross-sectional study employs convenient sampling technique and includes 200 female paramedical professionals working at govt and private hospitals after taking informed consent and ethical approval. Participants with no history of mental illness, and willing to participate were included in the study. An 8-item everyday discriminatory scale (EDS) was used to collect data. Descriptive statistics, ANOVA and Spearman Correlational Coefficient were used to analyze data by using IBM SPSS version 26. Results: The study comprises 200 female paramedical professionals with the largest proportion 43.0% aged 25 to 34. Spearman coefficient revealed a significant negative correlation (r=-0.321, p< 0.0001) with pay scale and significant positive correlation with age. proportion of respondents reported facing various forms of discrimination. Comparably, Nurses experienced higher discrimination. Conclusion: The results of the study emphasize the need to actively take actions against discriminatory behaviors towards female paramedics. It is particularly important to focus on preventive strategies of discrimination against nurses, as they are the most vulnerable to experience discrimination among all female healthcare professionals in the paramedic field.